Social reconstruction and healing of traumatized communities - Ajduković, Dean (Array, 2004)
Massive violence does not happen in social isolation but it is designed to cause horror, hurt people and destroy their belief systems and send specific messages to the victimized populations. The feeling of predictability of the world as the victims knew it is gone, while at the same time support mechanisms are typically far from adequate. The social context of trauma recovery in a destabilized community is loaded with high levels of uncertainty, frustration, anger, aggression and fear, helplessness and feelings of being discriminated. In such contexts effective community-based interventions that facilitate social reconstruction, decrease social tensions among groups that have been involved in a conflict, and provide treatment for the most traumatized individuals are the vehicle for people to integrate painful collective experiences so that they can turn toward the future. Parallel to this, capacity building of the care-providers is essential, as their traditional clinical roles extend into new social realm. Several models describing the essential processes in the social reconstruction and trauma healing will be presented, and barriers related to recovery from trauma, such as fragmentation of social life, deep feelings of distrust, complicated grieving, perceptions of being betrayed by the people one has trusted will be discussed.